Standardization of the dry extract having anti-inflammatory and analgesic properties from the leaves Arctium tomentosum Mill - V. V. Dudko; T. G. Khoruzhaya; V. G. Pashinsky; T. N. Povetyeva; T. P. Novozheyeva; N. Ye. Korshounova (Бюллетень сибирской медицины)
The work is devoted to the problems of obtaining dry and liquid extracts from the leaves of Arctium tomentosum Mill. on 25, 40, and 70% ethanol solution and their standardization. Optimal content of tablet drug form based on the dry extract on 70% ethanol is offered. Animal experiments revealed anti-exudative activity of the dry extract of А rctium tomentosum Mill.on 70, 40 и 25% of ethanol solution, analgesic activity of the dry extract on 70 and 25% of ethanol solution, wound healing action of the dry extract on 25% of ethanol solution .